PREVALENCE OF CELIAC DISEASE AMONG CHILDREN WITH SHORT STATURE IN A TERTIARY CARE HOSPITAL. - Mahli, Rajiv Kumar; Kumar, Anil; Anand, Chhitiz (Student’s Journal of Health Research Africa, 2024)
Background Celiac disease (CD), triggered by gluten and tissue transglutaminase, commonly affects the small intestine, with extra-intestinal manifestations like short stature emerging, prompting this study to assess its prevalence among patients with short stature. Objectives of the Study (1) To show the prevalence of celiac disease among children with short stature. (2) To show the effect of dietary restrictions in children with celiac disease on height. Methods A retrospective cross-sectional study included children assessed for short stature, whose medical records were analyzed. IgA tTG levels were determined using enzyme immunoassay, with concentrations >20U/mL considered positive. Those with positive results underwent standard celiac disease investigations, including endoscopy and biopsy. Results Medical documents of 103 patients with short stature were evaluated. 40 of them were included in the study according to inclusion criteria; 26(65%) were female and 14 (35%) were male. Median age was 9 years (from 2 - 18 years). The anti-tTG assays were positive in 20% of patients (8/40). Out of 8 patients who had positive titers of anti-tTG, 6 (75%) were diagnosed with celiac disease by endoscopy and biopsy according to the modified Marsh classification. All children diagnosed with celiac disease were kept on a gluten-free diet. Follow-up anthropometric data for six months as recorded in medical documents were analyzed and showed improvement in growth rates. Conclusion Celiac disease is a cause of short stature that should be included in diagnostic investigations of short stature. Recommendations Routine screening for celiac disease in children with short stature, even without digestive symptoms, is essential, as evidenced by a 20% prevalence rate in this study. Implementing a gluten-free diet resulted in improved growth rates, emphasizing the importance of dietary management in associated conditions.